1994
DOI: 10.1021/bi00193a004
|View full text |Cite
|
Sign up to set email alerts
|

1H and 15N Resonance Assignment and Secondary Structure of Capsicein, an .alpha.-Elicitin, Determined by Three-Dimensional Heteronuclear NMR

Abstract: The backbone 1H and 15N resonance assignments and solution secondary structure determination of capsicein, a protein of 98 residues with a molecular mass of 10161 Da, are presented. Capsicein belongs to the elicitin family, elicitor molecules having toxic and signaling properties that are secreted by Phytophthora fungi, responsible for the incompatible hypersensitive reaction of diverse plant species leading to resistance against fungal or bacterial plant pathogens. The protein was uniformly labeled with 15N t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Three disulfide bridges (Cys3-Cys71, Cys27-Cys56, and Cys5I-Cys95) were established by NMR in / 3 cqptogein and are similar to those previously identified in capsicein (Bouaziz et al, 1994a(Bouaziz et al, , 1994b. The first one, linking a1 to the p-sheet, was also assessed by chemical means.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Three disulfide bridges (Cys3-Cys71, Cys27-Cys56, and Cys5I-Cys95) were established by NMR in / 3 cqptogein and are similar to those previously identified in capsicein (Bouaziz et al, 1994a(Bouaziz et al, , 1994b. The first one, linking a1 to the p-sheet, was also assessed by chemical means.…”
Section: Resultsmentioning
confidence: 59%
“…In vivo "N-labeling of p cryptogein was performed according to that of capsicein (Bouaziz et al, 1994b), except that I5N glycine was used as nitrogen source instead of nitrate. Samples were prepared by dissolving lyophilized unlabeled or ISN-labeled cryptogein in 0.3 mL at a 3mM concentration in H20/D20 (9:l) or and analyzed using FELIX (95.0).…”
Section: Methodsmentioning
confidence: 99%
“…Literature searches revealed that the secondary structure, disulfide bonds and some other long-range contacts, were determined for a close homologue of the target sequence. 13 No fold in SCOP was compatible with these data, so we were very confident in our ''negative'' prediction. In the other three new fold targets, T0005, T0010, and T0016, we could not rule out the possibility of distant relationship to known structures; therefore, with a different degree of confidence, we assigned a single SCOP superfamily for each of these targets.…”
Section: Predictions and Comparison With The Experimental Structuresmentioning
confidence: 52%
“…A BLAST search 14 returned an alignment of the last 87 (out of 98), residues of T0032 to the alpha-elicitin capsicein protein (Swissprot ID: P15571) with 86% sequence identity. The secondary structure of this alpha-elicitin capsicein protein had already been determined by NMR spectroscopy by Bouaziz et al 15 As the sequence identity was quite high over an extended region, the secondary structure of T0032 was simply predicted to be identical to the NMR assignment of alpha-elicitin, and consisting of five alpha helices and two strands. This predicted sequence achieved the prediction accuracy Q3 ϭ 79.6%, with 97.8% of secondary structure elements correctly predicted.…”
Section: Prediction Of Beta-cryptogein (T0032)mentioning
confidence: 96%